Allelopathic potential from cover crops aqueous extract on weeds and maize (Research, Society and Development, 2020)
Cover crops are used as a strategy to recover degraded soils, improving their physical, chemical and biological characteristics, as well as assisting in the control of weeds through allelochemical compounds released by the shoot degradation process. This work aimed to evaluate the phytotoxicity of the aqueous extract of the cover crops Raphanus sativus L., Avena strigosa (Schreb) and Vicia villosa R. on the germination and initial growth of Zea mays, Amaranthus spinosus L. and Ipomoea grandifolia (Dammer) O'Donnell, as well as to identify and quantify the phenolic compounds present in the extract. Straws from the dried and crushed cover crops were used. The extracts were obtained by mixing 10% R. sativus and A. strigosa, and 12% V. villosa in distilled water (m/v). DIC was used, with four replications, in a 3x4 factorial scheme, with 3 cover crops (R. sativus, A. strigosa and V. villosa) and 4 concentrations (0%, 25%, 50% and 75%). The variables analyzed were: germination, germination speed index (GSI), seedling growth, root protrusion (RP), root protrusion speed index (RPSI) and dry mass of the root and shoot. Higher concentrations of the extracts affected the initial development of maize and weeds. The phenolic compounds identified in greater quantity were benzoic acid, p-coumaric acid, followed by ferulic acid and p-hydroxybenzoic acid. It is suggested that studies of the same nature be carried out in the field, since the interactions between soil microorganisms, climatic conditions can interfere with the results.